The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3389/fgene.2019.00531
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Revealed Novel Non-proliferative Retinopathy Specific Circulating MiRNAs in T2DM Patients

Abstract: Background: Diabetic retinopathy (DR) is a common diabetes complication and was considered as the major cause of blindness among young adults. MiRNAs are a group of small non-coding RNAs regulating the expression of target genes and have been reported to be associated with the development of DR in a variety of molecular mechanisms. In this study, we aimed to identify miRNAs that are differentially expressed (DE) in the serum of DR patients. Methods: We recruited 21 type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…miRNAs and long non-coding RNA, which are well-known for their regulatory functions, are gaining more attention. Several studies identified panels of miRNAs whose expressions are changed in the retinal ECs of diabetic rats (184)(185)(186) (188). These miRNAs were found to regulate 55 target genes which were involved in controlling the vascular growth and morphogenesis.…”
Section: Mirnasmentioning
confidence: 99%
“…miRNAs and long non-coding RNA, which are well-known for their regulatory functions, are gaining more attention. Several studies identified panels of miRNAs whose expressions are changed in the retinal ECs of diabetic rats (184)(185)(186) (188). These miRNAs were found to regulate 55 target genes which were involved in controlling the vascular growth and morphogenesis.…”
Section: Mirnasmentioning
confidence: 99%
“…In similar studies, miR-21, miR-181c, and miR-1179 were significantly upregulated in type 2 diabetic patients with proliferative DR vs. patients with non-proliferative DR (25), while miR-3197 and miR-2116-5p were higher in diabetic patients with DR, compared with patients without DR (37). In addtion, using an RNA-Seq approach, it was evidenced that miR-4448, miR-338-3p, miR-190a-5p, miR-485-5p, and miR-9-5p appeared differentially expressed in serum from retinopathic diabetic patients when compared to controls (49). However, while validation of miR-21 and miR-126 in DR was confirmed in other similar studies (39,40,44,45), miR-320a, which was previously found to be upregulated in DR (23), was later reported to be significantly downregulated in another work (51), indicating, therefore, that discrepancies exist in this context.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, several works have investigated the association of miRNAs with DR (23)(24)(25)(26)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). In circulating miRNA profiling studies, miR-27b, miR-320a, and miR-126 were validated in patients with type 1 diabetes and DR (23,42).…”
Section: Discussionmentioning
confidence: 99%
“…It is very encouraging to see that our findings have been confirmed by different groups using different techniques. However, there are studies that identify completely different sets of biomarkers, such as RNA-seq study of non-proliferative DR biomarkers for DRII patients in Chinese Han ancestry in serum [ 46 ]. This kind of result poses questions of the variability between ethnic groups and redundancy of the miRNA family member function.…”
Section: Discussionmentioning
confidence: 99%